PENGARUH MEDIA AUGMENTED REALITY BERBANTUAN ASSEMBLR EDU PADA MATERI INDONESIAKU KAYA BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD - Lestari, Adinda; Kadir, Dalimawaty; Rapita Silalahi, Beta; Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning media for the IPAS (Natural and Social Sciences) subject often lacks appeal,leadingstudentstoprefertechnology-basedmedia.Thisstudyaimedto determinetheeffectofusingAugmentedRealitymediasupportedbyAssemblr EduontheIPASlearningoutcomesspecificallyregardingthetopic"Indonesia's Rich Culture"among fourth-grade students at SDN 101868 Batang Kuis. The study employed a quantitative approach using an experimental method involving 48 fourth-grade students. Data were collected through learning outcome tests, interviews, documentation, and questionnaires administered before and after the intervention. Statistical tests were used for data analysis. TheresultsshowedanN-Gainscoreof0.624fortheexperimentalclass,which was higher than the 0.365 score recorded for the control class. These findings indicate that the use of Augmented Reality media supported by Assemblr Edu has a positive effect on improving student learning outcomes in the IPAS subject, specifically for the "Indonesia's Rich Culture" topic